SCR zeolite catalysts for reduced N2O formation
By optimizing the atomic ratios of copper, calcium, magnesium and other metals in the CHA type diamond hole catalyst, the problems of low temperature NOx removal efficiency and insufficient catalyst stability in the prior art are solved, and efficient and stable nitrogen oxide removal effect is achieved.
Patent Information
- Application Number
- JP2024555985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-23
- Filing Date
- 2023-03-23
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has low efficiency in removing nitrogen oxides (NOx) under low temperature conditions, and the SCR catalyst is not stable enough in high temperature and water vapor environments, making it difficult to meet the requirements of modern engine emission standards.
Small-pore diamond hole (CHA) type diamond hole catalyst promoted by copper, metal M1 and metal M2 is used to improve the low-temperature activity and water vapor stability of the catalyst by optimizing the atomic ratio of copper, calcium, magnesium and other metals.
It has achieved efficient nitrogen oxide removal, especially under low temperature conditions, and the stability of the catalyst in high temperature and water vapor environment has been greatly improved, meeting the requirements of modern engine emission standards.
Smart Images

Figure 2025509904000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to catalytically active compositions for selective catalytic reduction of nitrogen oxides from the exhaust gases of combustion engines. The present invention relates to small pore zeolites promoted with copper, metal M1 and metal M2, where metal M1 is calcium, magnesium or strontium and metal M2 is selected from calcium, magnesium, barium, strontium, yttrium, titanium, zirconium, niobium, iron, zinc, silver, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and mixtures thereof, where M1 and M2 are not identical. Methods for producing these catalytically active compositions and their uses are also envisaged. [Background technology]
[0002] Zeolites are crystalline microporous aluminosilicate materials formed by corner-sharing TO4 tetrahedra, where T represents silicon (Si) or aluminum (Al), which are interconnected by oxygen atoms to form pores and cavities of uniform size and shape precisely defined by the crystal structure. Zeolites are also called "molecular sieves" because the pores and cavities are similar in size to small molecules. This class of materials has important commercial applications as adsorbents, ion exchangers and catalysts.
[0003] Zeolites are classified by the International Zeolite Association (IZA) according to the rules of the IUPAC Commission on Zeolite Nomenclature. Once a new framework topology is established, a three-letter code is assigned. This code defines the atomic structure of the framework and can then explain distinct X-ray diffraction patterns.
[0004] It is also common to classify zeolites according to their pore size, which is defined by the ring size of the largest pore opening. Zeolites with large pore size have a maximum ring size of 12 tetrahedral atoms, zeolites with medium pore size have a maximum pore size of 10, and zeolites with small pore size have a maximum pore size of 8 tetrahedral atoms. Well-known small pore zeolites belong in particular to the AEI, CHA (chabazite), ERI (erionite), LEV (levin) and KFI framework types. An example with large pore size is the faujasite framework type zeolite.
[0005] A large number of molecular sieve structures are known today. Some known molecular sieves belong to specific families of structures with similar characteristics. One particular family, the ABC-6 family, can be described as a stacking of two-dimensional periodic layers of unconnected planar six-ring motifs, composed of six T atoms (T=Si, Al, etc.) connected by oxygen atoms. The resulting layers, with hexagonal symmetry, are also called periodic building units (PerBUs). The stacking is typically described by a sequence of letters "A", "B", and "C", which indicate the relative positions of adjacent layers. "A", "B", and "C" refer to the well-known relative positions of adjacent layers when stacking hexagonal layers of close-packed spheres.
[0006] The CHA framework belongs to the ABC-6 family and can be described by a repeating stacking sequence of AABBCC, which results in a framework topology characterized by a three-dimensional eight-ring pore system containing double six-membered rings (d6R) and cha cages.
[0007] Small pore zeolites, especially when cations such as copper and iron are contained in the zeolite pores, play an important role as catalysts in the so-called Selective Catalytic Reduction (SCR) of nitrogen oxides with ammonia to form nitrogen and water. The SCR process has been widely used to purify exhaust gases resulting from the combustion of fossil fuels, especially from stationary power plants and vehicles powered by diesel engines.
[0008] NO by NH3 x The catalytic reduction of NO can be represented by different reaction equations. Nitric oxide (NO) is the main NO produced in the engine. x The reduction of NO is called the "standard" NH3-SCR reaction: 4NO+4NH3+O2→4N2+6H2O(1)
[0009] NO2 is more reactive than NO. In the presence of a mixture of NO and NO2, the NH3-SCR reaction is more facile and the so-called "fast" NH3-SCR reaction may occur: 2NH3+NO+NO2→2N2+3H2O(2)
[0010] To take advantage of the fast NH3-SCR reaction, an additional catalyst is needed to oxidize a portion of the NO to NO2.
[0011] Also, side reactions can occur resulting in undesirable products or unproductive consumption of ammonia. 4NH3+3O2→N2+6H2O(3) 2NH3+2O2→N2O+3H2O(4) 4NH3+5O2→4NO+6H2O(5) 4NH3+7O2→4NO2+6H2O(6) 2NH3+2NO2+H2O→NH4NO2+NH4NO3(7)
[0012] In the official driving cycle, the exhaust gas temperatures of the latest generation engines and hybrid vehicles, which have reduced fuel consumption and low CO2 emissions, are significantly lower than those of previous engine generations. x It is necessary to obtain NH3-SCR catalysts that show better low-temperature NO conversion than their Fe-containing counterparts. x The conversion rate is shown. Furthermore, the NH3-SCR catalyst shall emit as little N2O as possible. Next to selectivity and activity, the hydrothermal stability of the SCR catalyst is another essential parameter, since it should withstand extreme temperature conditions under full engine load and exposure to water vapor at temperatures up to 700°C is known to be critical for many zeolite types.
[0013] WO 2019 / 223761(A1) discloses a rare-element-containing zeolite material having a framework structure selected from the group consisting of AEI, AFT, AFV, AFX, AVL, CHA, EMT, GME, KFI, LEV, LTN and SFW, and including a mixture of two or more of these. Preferably, the zeolite material has an AEI or CHA framework structure. The framework structure of the zeolite material comprises SiO2 and X2O3, where X represents a trivalent element, and the zeolite material exhibits a SiO2:X2O3 molar ratio in the range of 2 to 20, and the zeolite material contains one or more rare earth elements as counterions at the ion exchange sites of the framework structure. X is selected from the group consisting of Al, Ga and mixtures thereof. The zeolite material preferably contains one or more transition metals, preferably selected from the group consisting of Fe, Cu, Pt and Pd. Additionally, the zeolitic material contains one or more rare earth elements selected from the group consisting of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc, most preferably Yb, Lu, Y and Sc, with Y being more preferred than the other rare earth elements.
[0014] In "Rare-earth ion exchanged Cu-SSZ-13 zeolite from organotemplate-free synthesis with enhanced hydrothermal stability in NH3-SCR of NOx" Z Zhao, R Yu, C Shi, H Gies, FS Xiao, D De Vos, T Yokoi, X Bao, U Kolb, R McGuire, AN Parvulescu, S Maurer, U Muller and W Zhang, the effect of rare earth ions on the hydrothermal stability and NO conversion of Cu-SSZ-13 was examined. SSZ-13 zeolites with Si / Al ratios of 4 and 5, corresponding to SAR values of 8 and 10, were ion-exchanged with Ce, La, Sm, Y or Yb and then with copper. The zeolites thus obtained had a copper content of 2.2% to 3.4% by weight and a rare earth metal content of 0% to 2.7% by weight. The NO conversion of SSZ-13 zeolite was tested after hydrothermal treatment at 800 °C for 16 h in 10% H2O / air. All zeolites enriched with rare earth metal ions showed improved low-temperature NO conversion when compared to zeolites containing only copper. Among the rare earth ions tested, yttrium showed a significant improvement in hydrothermal stability and NH3-SCR activity after hydrothermal aging of Cu-SSZ-13. However, the behavior of rare earth metal exchanged zeolites in high-rate SCR reactions and their selectivity for NO was not examined.
[0015] European Patent Application No. 2659973(A1) discloses a chabazite-type zeolite carrying copper and an alkaline earth metal. The alkaline earth metal is preferably at least one metal selected from the group consisting of calcium, magnesium, and barium. The SiO2 / Al2O3 molar ratio is preferably 10 to 50, and the copper / aluminum atomic ratio is preferably 0.15 to 0.25. This type of chabazite-type zeolite exhibits a higher nitrogen oxide purification rate after hydrothermal durability treatment than conventional chabazite-type zeolite catalysts carrying only copper.
[0016] WO 2013 / 155244 A1 provides a catalytic material useful for selective catalytic reduction of NOx in lean combustion exhaust gas, which is a hydrothermally stable, low SAR aluminosilicate zeolite supported with a synergistic combination of one or more transition metals, such as copper, and one or more alkaline earth metals, such as calcium or potassium. Preferably, the aluminosilicate zeolite is CHA, with an SAR value of 10-25. The zeolite is promoted with a base metal selected from Cr, Mn, Fe, Co, Ni, and Cu and mixtures thereof, and a second promoter metal selected from Na, K, Rb, Cs, Mg, Ca, and Ba. An example shows chabazite exchanged with copper and a second metal selected from one of Na, K, Cs, Mg, Ca, Sr, or Mn. The molar ratios of the first and second promoter metals to aluminum are not given for each individual promoter metal or for their sum.
[0017] WO 2019 / 219623(A1) provides a hydrothermally stable crystalline aluminosilicate zeolite having a CHA framework type, the zeolite having a total proton content of less than 2 mmol per gram. The zeolite may contain at least one transition metal, calculated as the respective oxide and based on the total weight of the zeolite, in an amount of 0.1% to 10% by weight. Preferably, it is Cu and / or Fe, and most preferably Cu. The zeolite may further contain at least one alkali metal or alkaline earth metal, calculated as the respective metal and based on the total weight of the zeolite, in a concentration of 0% to 2% by weight. The alkali or alkaline earth metal is preferably Na and / or K. The present invention further provides a one-pot synthesis method for producing an aluminosilicate zeolite having a CHA framework type. The aqueous reaction mixture containing the tetraethylammonium compound, a silica source, at least one alkali metal hydroxide or alkaline earth metal hydroxide, a faujasite framework-type zeolite, and Cu-tetraethylenepentamine is mixed, homogenized, heated, and finally the product is recovered. The novel hydrothermally stable zeolite containing the CHA framework-type is suitable as a catalytically active material for selective catalytic reduction of nitrogen oxides by reaction with NH3 as a reductant (NH3-SCR), in which the hydrothermally stable zeolite is used.
[0018] US Patent Application Publication No. 2014 / 112853(A1) discloses compositions and catalytic articles comprising copper promoted 8-ring small pore molecular sieves and iron promoted 8-ring small pore molecular sieves. The catalytic articles are useful in methods and systems for catalyzing the reduction of nitrogen oxides in the presence of a reducing agent. The zeolite is preferably selected from AEI, AFT, AFX, CHA, EAB, ERI, KFI, LEV, SAS, SAT, and SAV, and most preferably the zeolite is CHA. The copper promoted 8-ring small pore molecular sieves can include an alkaline earth metal selected from barium, magnesium, beryllium, calcium, strontium, radium, and combinations thereof. Preferably, the alkaline earth metal is selected from barium, magnesium, calcium, and combinations thereof. Most preferably, the alkaline earth metal is barium. The composition exhibits significantly lower low-temperature DeNO at lower NH3 loading levels than the copper-promoted Cu-SSZ-13 most often used in existing SCR catalysts. x Improved performance and low N2O selectivity are shown.
[0019] WO 2014 / 062952(A1) describes a selective catalytic reduction catalyst comprising an 8-ring small pore molecular sieve promoted with copper and alkaline earth components. The catalyst is capable of reducing nitrogen oxides (NO x ) is effective in catalyzing the reduction of nitrogen oxides. A method for selectively reducing nitrogen oxides is also described. The zeolite is selected from AEI, AFT, AFX, CHA, EAB, ERI, KFI, LEV, SAS, SAT, and SAV, preferably the zeolite is CHA. The alkaline earth metal is selected from barium, magnesium, beryllium, calcium, strontium, radium, and combinations thereof. Preferably, the alkaline earth metal is selected from barium, magnesium, calcium, and combinations thereof. Most preferably, the alkaline earth metal is barium. The composition provides improved low temperature DenO at significantly lower NH3 loading levels than the copper promoted Cu-SSZ-13 most often used in existing SCR catalysts. xWO 2014 / 062952(A1) does not mention the N2O selectivity of the disclosed catalysts.
[0020] WO 2015 / 189680A1 describes a base metal catalyst that generates heat over a temperature range of 300°C to 650°C and includes an effective amount of base metal material to oxidize soot captured by a downstream particulate filter. The base metal catalyst is substantially free of platinum group metals. The base metal catalyst can be used to reduce nitrogen oxides (NO x Also described are emissions treatment systems and methods for removing uranium, particulate matter, and gaseous hydrocarbons. The base metal material is selected from V, W, Ti, Cu, Fe, Co, Ni, Cr, Mn, Nd, Ba, Ce, La, Pr, Mg, Ca, Zn, Nb, Zr, Mo, Sn, Ta, Ce, and Sr, and combinations thereof. The catalyst may further include a molecular sieve selected from AEI, AFT, AFX, CHA, EAB, EMT, ERI, FAU, GME, JSR, KFI, LEV, LTL, LTN, MOZ, MSO, MWW, OFF, SAS, SAT, SAV, SBS, SBT, SFW, SSF, SZR, TSC, WEN, and combinations thereof.
[0021] The main drawback of state-of-the-art copper-loaded zeolites is that the copper loading must be high enough to obtain acceptable performance in SCR reactions after aging, but high copper loading of the zeolite leads to high NO levels, which makes it difficult to meet regulatory emission limits. The prior art showed that reducing the amount of copper reduces the NO levels, but not the NO x The conversion rate also decreases. When other transition metals or rare earth metals are added to such zeolites with reduced copper content, the NO x The conversion increases but is still lower than the copper-rich zeolite alone.
[0022] There is a continuing need for improved SCR catalysts that exhibit not only good activity for converting nitrogen oxides, but also good selectivity, meaning that as many of the nitrogen oxides as possible are converted to nitrogen according to equations (1) and (2) above, and not converted to NO, NO2, NO or ammonium nitrite and ammonium nitrate according to equations (4)-(7). Summary of the Invention [Problem to be solved by the invention]
[0023] The object of the present invention is to provide a catalytically active composition for removing nitrogen oxides from the exhaust gases of a combustion engine, which has a high NO x It is an object of the present invention to provide a catalytically active composition which exhibits a high conversion rate and good selectivity for nitrogen for this conversion. It is another object of the present invention to provide an apparatus and system for treating the exhaust gas of a combustion engine which comprises the catalytically active composition according to the present invention. It is yet another object of the present invention to provide a method for treating NO from the exhaust gas of an internal combustion engine. x The objective is to provide a method for reducing emissions, and optionally also particulate matter. [Means for solving the problem]
[0024] The object of providing a catalytically active composition for removing nitrogen oxides from the exhaust gases of combustion engines, which exhibits a high NOx conversion rate, together with good durability, as well as a good selectivity towards nitrogen for this conversion, is solved by a crystalline aluminosilicate small pore zeolite having a maximum ring size of 8 tetrahedral atoms, the zeolite being copper, the Cu:Al atomic ratio being between 0.12 and 0.55; a metal M1, where M1 is calcium, magnesium or strontium and the M1:Cu atomic ratio is between 0.05 and 0.95; a metal M2 selected from magnesium, calcium, barium, strontium, yttrium, titanium, zirconium, niobium, iron, zinc, silver, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and mixtures thereof, the M2:Cu atomic ratio being between 0.05 and 0.80, - M1 and M2 are different from each other, the total atomic ratio of copper, metal M1, and metal M2 to aluminum, (Cu+M1+M2):Al, is 0.20 to 0.80; The zeolite contains at least 2.5% by weight copper, calculated as CuO, based on the total weight of the zeolite.
[0025] A catalytically active composition for removing nitrogen oxides from the exhaust gas of a combustion engine, as well as an apparatus and a system for treating the exhaust gas of a combustion engine comprising the catalytically active composition, are described below, the invention including all of the embodiments set out below, both individually and in combination with one another.
[0026] Selective catalytic reduction of nitrogen oxides is hereinafter referred to as "SCR" or "SCR reaction".
[0027] A "catalytically active composition" is a substance or mixture of substances capable of converting one or more components of an exhaust gas into one or more other components. An example of such a catalytically active composition is, for example, an oxidation catalyst composition capable of converting volatile organic compounds and carbon monoxide into carbon dioxide or ammonia into nitrogen oxides. Another example of such a catalyst is, for example, a selective catalytic reduction catalyst (SCR catalyst) composition capable of converting nitrogen oxides into nitrogen and water. In the context of the present invention, an SCR catalyst is a catalyst comprising a support substrate and a washcoat comprising an SCR catalytically active composition. An ammonia slip catalyst (ASC) is a catalyst comprising a support substrate, a washcoat comprising an oxidation catalyst and a washcoat comprising an SCR catalytically active composition.
[0028] Molecular sieves are materials with uniformly sized pores, i.e., very small holes. The diameter of these pores is similar in size to small molecules, so that larger molecules cannot enter or adsorb, but smaller molecules can. In the context of the present invention, molecular sieves are zeolites. Zeolites consist of corner-sharing tetrahedral SiO4 and AlO4 units. They are also called "silicoaluminates" or "aluminosilicates". In the context of the present invention, these two terms are used synonymously.
[0029] As used herein, the term "non-zeolitic molecular sieve" refers to a corner-sharing tetrahedral framework in which at least some of the tetrahedral moieties are occupied by elements other than silicon or aluminum. When some, but not all, of the silicon atoms are replaced by phosphorus atoms, it is referred to as a "silicoaluminophosphate" or "SAPO". When all of the silicon atoms are replaced by phosphorus, it is referred to as an aluminophosphate or "AlPO".
[0030] "Zeolite framework types", also called "framework types", represent a corner-sharing network of tetrahedrally coordinated atoms. It is common to classify zeolites according to their pore size, which is defined by the ring size of the largest pore opening. Zeolites with large pore sizes have a maximum ring size of 12 tetrahedral atoms, zeolites with medium pore sizes have a maximum pore size of 10, and zeolites with small pore sizes have a maximum pore size of 8 tetrahedral atoms. Known small pore zeolites belong in particular to the AEI, CHA (chabazite), ERI (erionite), LEV (levinite), AFX and KFI frameworks. Examples with large pore sizes are zeolites of the framework type faujasite (FAU) and zeolite beta (BEA).
[0031] A "zeotype" includes any of a family of materials based on the structure of a particular zeolite. Thus, a particular "zeotype" includes, for example, silicoaluminates, SAPOs, and AIPOs based on the structure of a particular zeolite framework type. Thus, for example, chabazite (CHA), silicoaluminates SSZ-13, Linde R, and ZK-14, silicoaluminophosphate SAPO-34, and aluminophosphate MeAlPO-47 all belong to the chabazite framework type. Those skilled in the art know which silicoaluminates, silicoaluminophosphates, and aluminophosphates belong to the same zeotype. Furthermore, zeolites and non-zeolitic molecular sieves that belong to the same zeotype are listed in the database of the International Zeolite Association (IZA). Those skilled in the art can use this knowledge and the IZA database without departing from the scope of the claims.
[0032] The silica to alumina ratio (SiO2:Al2O3) of a zeolite is hereinafter referred to as the "SAR value."
[0033] A "catalyst support substrate," also referred to simply as a "support substrate," is a support onto which a catalytically active composition is deposited to form the final catalyst. As such, the support substrate is a support for the catalytically active composition.
[0034] A "washcoat" as used herein is an aqueous suspension of a catalytically active composition and, optionally, at least one binder. Suitable binder materials are, for example, aluminum oxide, titanium dioxide, silicon dioxide, zirconium dioxide, cerium dioxide, or mixtures thereof, such as a mixture of silica and alumina.
[0035] A washcoat applied to a catalyst support substrate is called a "coating". It is also possible to apply more than one washcoat to a support substrate. It is known to those skilled in the art that more than one washcoat can be applied to a single support substrate by "layering" or "zoning", and it is also possible to combine layering and zoning. In the case of layering, the washcoats are applied one after the other on the support substrate. The washcoat applied first and thus in direct contact with the support substrate is the "underlayer", and the washcoat applied last is the "upper layer". In the case of zoning, a first washcoat is applied on the support substrate from a first face side A of the support substrate towards the other face side B, but not over the entire length of the support substrate, but only up to the end point between face sides A and B. Then, a second washcoat is applied on the support substrate starting from face side B to the end point between face sides B and A. The end points of the first and second washcoats do not have to be the same, and if they are the same, both washcoat zones are adjacent to each other. However, if the endpoints of two washcoat zones, both located between face sides A and B of the carrier substrate, are not the same, there may be a gap between the first and second washcoat zones or they may overlap. As mentioned above, layering and zoning can also be combined, for example, if one washcoat is applied over the entire length of the carrier substrate and the other washcoat is applied only from one face side to an endpoint between both face sides.
[0036] In the context of this invention, "washcoat loading" is the mass of catalytically active composition per volume of support substrate.
[0037] Those skilled in the art will appreciate that washcoats are prepared in the form of suspensions and dispersions.
[0038] Suspensions and dispersions are heterogeneous mixtures comprising solid particles and a solvent. The solid particles do not dissolve but are suspended throughout the volume of the solvent and remain freely suspended in the medium. If the solid particles have an average particle size of 1 μm or less, the mixture is called a dispersion, and if the average particle size is greater than 1 μm, the mixture is called a suspension. A washcoat in the sense of the present invention comprises a solvent, usually water, suspended or dispersed particles represented by particles of one or more catalytically active compositions, and optionally particles of at least one binder as described above. This mixture is often called a "washcoat slurry". The slurry is applied to a support substrate and subsequently dried to form the coating described above. In the context of the present invention, the term "washcoat suspension" is used for a mixture of a solvent and particles of one or more catalytically active compositions, and optionally particles of at least one binder, regardless of their individual or average particle size. This means that in the "washcoat suspension" of the present invention, the individual particle size as well as the average particle size of the one or more catalytically active solid particles may be less than, equal to and / or greater than 1 μm.
[0039] The term "mixture" as used in the context of the present invention is a material composed of two or more different substances physically combined, in which each component retains its own chemical properties and structure. Despite the fact that there is no chemical change in the components, the physical properties of the mixture, such as its melting point, may differ from those of the components.
[0040] A "catalyzed substrate monolith" is a support substrate comprising a catalytically active composition. The support may be coated with a washcoat comprising the catalytically active composition, the washcoat comprising the catalytically active composition and optionally at least one binder. Alternatively, the catalytically active composition may be a component of the support substrate itself.
[0041] A "device" as used in the context of the present invention is a piece of equipment designed to serve a specific purpose or perform a specific function. A catalytic device according to the present invention serves the purpose and has the function of removing nitrogen oxides from the exhaust gases of a combustion engine. A "device" as used in the present invention may consist of one or more catalysts, also called "catalytic articles" or "bricks", as defined above.
[0042] "Upstream" and "downstream" are terms relative to the normal flow direction of exhaust gases in the exhaust pipe. "Zone or catalyst 1 located upstream of zone or catalyst 2" means that zone or catalyst 1 is located closer to the exhaust gas source, i.e., closer to the motor, than zone or catalyst 2. The flow direction is from the exhaust gas source toward the exhaust pipe. Thus, in this flow direction, exhaust gases enter each zone or catalyst at its inlet end and exit each zone or catalyst at its outlet end.
[0043] As used in the context of the present invention, the term "nitrogen oxides" includes nitric oxide (NO), nitrogen dioxide (NO2) and nitrous oxide (NO2O). However, in contrast, nitrous oxide is also an oxide of nitrogen, but the term "NO x " includes only NO and NO2, but not N2O. However, this distinction between "nitrogen oxides" and "NOx" is widely used by those skilled in the art.
[0044] "NO x The term "conversion rate" as used in the context of the present invention refers to the NO conversion rate that does not take into account NO in the gas phase after the catalyst. x "NO selectivity" means the percent conversion of NO in the gas feed. x and the percent conversion of NH3 to N2O.
[0045] The NO selectivity can be calculated according to the following formula:
[0046]
number
[0047] "Catalytic activity" or simply "activity" is the increase in the rate of a chemical reaction brought about by the presence of a catalytically active composition.
[0048] Those skilled in the art know that the SCR reaction requires a reducing agent to reduce the nitrogen oxides to nitrogen and water. A suitable reducing agent is ammonia, and the SCR reaction in the presence of ammonia is known as "NH3-SCR". The ammonia used as the reducing agent can be made available by feeding liquid or gaseous ammonia or an ammonia precursor compound into the exhaust gas. If an ammonia precursor is used, it is pyrolyzed and hydrolyzed to form ammonia. Examples of such ammonia precursors are ammonium carbamate, ammonium formate, and preferably urea. Alternatively, the ammonia may be formed by catalytic reaction of an ammonia precursor in the exhaust gas.
[0049] Suitable crystalline aluminosilicate small pore zeolites having a maximum pore size of 8 tetrahedral atoms are, for example, ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, BIK, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, ESV, ETL, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, THO, TSC, UEI, UFI, VNI, YUG, ZON, and mixtures and intergrowths thereof.
[0050] In a preferred embodiment of the present invention, the crystalline small pore aluminosilicate zeolite has a maximum pore size of 8 tetrahedral atoms and is selected from AEI, AFT, AFX, CHA, DDR, ERI, ESV, ETL, KFI, LEV, UFI and mixtures and intergrowths thereof. In a more preferred embodiment, the zeolite is selected from AEI, CHA, AFX and LEV. Even more preferably, the zeolite is selected from AEI and CHA and mixtures and intergrowths containing at least one of these framework types. In a particularly preferred embodiment, the zeolite is AEI. In another particularly preferred embodiment, the zeolite is CHA.
[0051] A zeolite "intergrowth" comprises at least two different zeolite framework types, or two different zeolite compositions of the same framework type.
[0052] In "surface-intergrowth" zeolites, one framework structure grows on top of the other. Thus, "surface-intergrowth" represents a species of "intergrowth", and "intergrowth" is a genus.
[0053] Hereinafter, the "crystalline aluminosilicate small pore zeolite having a maximum pore size of eight tetrahedral atoms" will be referred to as "crystalline aluminosilicate zeolite".
[0054] When the crystalline aluminosilicate zeolite has a CHA framework type, it includes all zeotypes having a CHA framework type, so long as they are crystalline aluminosilicates. Such zeotypes are, for example, SSZ-13, LZ-218, Linde D, Linde R, Phi, ZK-14, with SSZ-13 being preferred.
[0055] When crystalline aluminosilicate zeolites have the AEI framework type, they include all zeotypes having the AEI framework type, provided that they are crystalline aluminosilicates. Such zeotypes are, for example, SSZ-39 and SIZ-8.
[0056] When crystalline aluminosilicate zeolites have the AFX framework type, they include all zeotypes having the AFX framework type, so long as they are crystalline aluminosilicates. Such zeotypes are, for example, SSZ-16.
[0057] When crystalline aluminosilicate zeolites have the LEV framework type, they include all zeotypes having the LEV framework type, so long as they are crystalline aluminosilicates. Such zeotypes are, for example, ZK-20, LZ-132 and Nu-3.
[0058] The crystalline aluminosilicate zeolite has an SAR value of 5-50, preferably 7-30, and more preferably 8-25.
[0059] The crystalline aluminosilicate zeolite contains copper, in which the atomic ratio of copper to aluminum, Cu:Al, is 0.12 to 0.55, preferably 0.15 to 0.50, and more preferably 0.18 to 0.45.
[0060] The crystalline aluminosilicate zeolite contains a metal M1, in which the molar ratio of M1 to copper, M1:Cu, is 0.05 to 0.95, preferably 0.10 to 0.90, and more preferably 0.20 to 0.80.
[0061] The crystalline aluminosilicate contains a metal M2, in which the molar ratio of M2 to copper, M2:Cu, is 0.05 to 0.80, preferably 0.10 to 0.70, and more preferably 0.15 to 0.60.
[0062] The total atomic ratio of copper, metal M1, and metal M2 to aluminum in the crystalline aluminosilicate zeolite, (Cu+M1+M2):Al, is 0.20 to 1.00, preferably 0.30 to 0.80, and more preferably 0.35 to 0.70.
[0063] The crystalline aluminosilicate zeolite contains at least 2.50 wt.% copper, calculated as CuO, based on the total weight of the zeolite. Preferably, the zeolite contains 2.5 wt.% to 8.0 wt.% copper, more preferably 2.5 wt.% to 7.5 wt.%, even more preferably 3.0 wt.% to 7.2 wt.%, and most preferably 3.0 wt.% to 6.0 wt.% copper, calculated as CuO, based on the total weight of the zeolite. The M1:Cu, M2:Cu and (Cu+M1+M2):Al atomic ratios apply for these ranges of copper weight percent.
[0064] The metal M1 is calcium, magnesium or strontium, and mixtures thereof, preferably calcium or magnesium.
[0065] The metal M2 is selected from magnesium, calcium, barium, strontium, yttrium, titanium, zirconium, niobium, iron, zinc, silver, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, and mixtures thereof.
[0066] The metals M1 and M2 are different from each other. This means that M1 and M2 must not both be calcium, or both be magnesium, or both be strontium at the same time. However, it is possible for both M1 and M2 to represent alkaline earth metals, e.g. M1 being calcium and M2 being magnesium, or vice versa, as long as M1 and M2 do not represent the same alkaline earth metal.
[0067] In a preferred embodiment, M1 is calcium or magnesium and M2 is selected from iron, cerium, zirconium, yttrium, samarium, strontium, lanthanum or barium, the amounts of each metal being as indicated above. More preferably, M1 is calcium and M2 is selected from iron, cerium, zirconium, yttrium, samarium, strontium, lanthanum and mixtures thereof.
[0068] The "total weight of zeolite" is the weight of white zeolite plus the weight of copper, metal M1, and metal M2, the weights of copper, metal M1, and metal M2 being calculated as their respective oxides. "White zeolite" is a zeolite consisting of TO4 tetrahedra that does not contain copper, metal M1, or metal M2. Such zeolites are colorless due to the absence of transition metals, and are also called "white", giving the zeolite a color, for example, blue when copper is supported, or red when iron is supported, or mixed colors when two or more transition metals, such as copper and iron, are present. Those skilled in the art know that "white zeolites" usually contain protons and alkali metal cations, although often in trace amounts. However, protons and alkali metals do not impart color to the zeolite. Thus, the term "white zeolite" also includes zeolites that contain protons and alkali metal cations.
[0069] The amounts of copper, metals M1 and M2 can be measured by ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy) or XRF (X-Ray Fluorescence Spectroscopy). A person skilled in the art knows how to carry out such analyses and can apply this knowledge to the zeolites according to the invention without departing from the scope of the claims.
[0070] Aluminosilicate chabazite and its zeotypes are commercially available. Methods for producing chabazite are disclosed, for example, in EP 2931406 (B1), US 2018 / 079650 (A1), WO 2017 / 080722 (A1), US 2018 / 127282 (A1) and WO 2018 / 189177 (A1). In general, the synthesis of aluminosilicate zeolites includes mixing a silicon source, an aluminum source, an alkali metal or alkaline earth metal hydroxide, water and at least one organic structure directing agent (OSDA), and optionally a salt, such as a copper salt or an iron salt. The mixture forms a gel, which is aged, heat treated, purified, and optionally calcined. Those skilled in the art know how to synthesize the aluminosilicate chabazite and its zeotypes. Some methods for producing aluminosilicate zeolites, particularly CHA, are also known to utilize OSDA, which is a complex of copper with organic polyamines, such as copper tetraethylenepentamine (Cu-TEPA). When such a complex of copper with organic polyamines is used, the zeolite obtained therefrom already contains copper. The same applies, mutatis mutandis, when the synthesis gel contains copper or iron salts, and in such cases the zeolite obtained by synthesis already contains copper or iron. However, in other cases, the synthesis gel does not contain copper or iron.
[0071] In the context of the present invention, the amounts of copper, M1 and M2 can be adjusted according to the respective amounts of metals Cu, M1 and M2 in the final zeolite as shown above by ion exchange methods. By "adjusted" it is meant that Cu, M1 and M2 can be introduced for the first time if they are not present in the zeolite when synthesized, or that if introduced during synthesis, their amounts can be increased or decreased, but their amounts are outside the range required for the crystalline aluminosilicate according to the invention. Increasing or decreasing the amount of metals is particularly relevant for copper and iron, if they are introduced by the synthesis method.
[0072] As mentioned above, it is well known that metal cations can be removed from or introduced into zeolites via ion exchange reactions. These ion exchange reactions are described below by way of example for the introduction or removal of copper cations. The skilled person knows how to adapt these ion exchange reactions to obtain zeolites according to the invention with the desired contents of copper, M1 and M2. The reactions described also include a step in which metal cations are removed via the introduction of ammonium cations, which are subsequently pyrolyzed during calcination.
[0073] Copper can be introduced, for example, by ion exchange. In the first step, an ammonium exchange is carried out to replace the alkali metal or alkaline earth metal cations with NH + In the second step, NH4 is removed from the zeolite framework by replacing it with a cation. + are replaced by copper cations. The copper content of the resulting copper-containing zeolite can be easily controlled by the amount of copper salt and the number of ion exchange procedures carried out. The copper content can be measured by ICP-AES or XRF as described above.
[0074] Copper and iron are also + It can be removed by liquid ion exchange with cations.
[0075] Methods for introducing ammonium, copper and iron cations, and methods for removing copper and iron cations, respectively, are well known to those skilled in the art. These methods can be applied to the zeolite according to the invention without departing from the scope of the claims. For example, ammonium cations can be easily introduced via liquid ion exchange, and copper cations can also be easily introduced via liquid ion exchange, incipient wetness impregnation or solid ion exchange.
[0076] For the introduction of copper cations, methods are presented exemplarily below, which are applicable to obtain zeolites according to the invention loaded with copper, metal M1 and metal M2.
[0077] Liquid Ion Exchange NH4 + Liquid ion exchange can be carried out by treating the zeolite with an aqueous solution of an ammonium salt, such as NH4Cl or NH4NO3.
[0078] Cu 2+ Liquid ion exchange can be carried out by treating the zeolite with an aqueous solution of a copper salt, such as copper acetate (Cu(Ac)2), copper nitrate (Cu(NO3)2), copper acetylacetonate (Cu(acac)2) or copper chloride (CuCl2). This procedure can be repeated multiple times to achieve the desired copper content.
[0079] It is clear to those skilled in the art that the copper to zeolite ratio in the liquid ion exchange can be adjusted according to the desired copper content of the final zeolite. Generally speaking, an aqueous solution with a higher copper content will produce a zeolite with a higher copper content. What copper concentration should be selected and how often the procedure should be repeated can be easily determined by those skilled in the art without departing from the scope of the claims.
[0080] Optionally, the ammonium exchanged zeolite can be heat treated to partially or completely remove the ammonium ions, followed by copper exchange as described above.
[0081] Incipient wetness impregnation An aqueous solution of a copper salt, such as copper acetate (Cu(Ac)2), copper nitrate (Cu(NO3)2) or copper chloride (CuCl2), is dissolved in an appropriate volume of water. The amount of copper salt is equal to the amount of copper desired in the zeolite. Incipient wetness impregnation is carried out at room temperature. The copper-exchanged zeolite is then dried at a temperature of 60-70°C for 8-16 hours, and the mixture is subsequently heated to a temperature in the range of 550-900°C.
[0082] Solid Ion Exchange Suitable copper salts are, for example, copper acetate (Cu(CH3COO)2), copper nitrate (Cu(NO3)2), copper chloride (CuCl2), copper(II) sulfate (CuSO4), copper(II) oxide (CuO), copper(I) oxide (Cu2O) and copper acetylacetonate (Cu(acac)2). The copper salt and the zeolite are mixed in the dry state, and the mixture is subsequently heated to a temperature in the range of 550-900°C. A process for producing zeolites containing metals is disclosed, for example, in US Patent Application Publication No. 2013 / 0251611 (A1). This method can be made into the zeolite of the invention without departing from the scope of the claims.
[0083] The ion exchange method exemplarily described above for exchanging copper and ammonium ions can be applied to the exchange of metals M1 and M2 as well. It is well known that the introduction of different metal ions, for example copper ions and ions of metals M1 and M2, can be carried out sequentially or by co-ion exchange. Sequential ion exchange means that different cations are introduced one after the other, for example by introducing copper in a first step, metal M1 in a second step and metal M2 in a third step. Co-ion exchange means that all cations, for example copper and metals M1 and M2, are exchanged together in one step. Sequential and co-ion exchange can also be applied when exchanging three or more different cations. The skilled person knows how to apply the ion exchange method exemplarily described above for the exchange of copper and ammonium ions to the exchange of other ions and can apply this knowledge to the present invention without departing from the scope of the claims.
[0084] Suitable magnesium salts for introducing magnesium via ion exchange are, for example, magnesium chloride (MgCl), magnesium nitrate (Mg(NO)), magnesium sulfate (MgSO), magnesium acetate (Mg(CHCOO) and magnesium acetylacetonate (Mg(acac)).
[0085] Suitable calcium salts for introducing calcium via ion exchange are, for example, calcium chloride (CaCl2), calcium nitrate (CaNO3), calcium acetate (Ca(CH3COO)2) and calcium acetylacetonate (Ca(acac)2).
[0086] Suitable barium salts for introducing barium via ion exchange are, for example, barium chloride (BaCl2), barium nitrate (Ba(NO3)2), barium acetate (Ba(CH3COO)2) and barium acetylacetonate (Ba(acac)2).
[0087] Suitable strontium salts for introducing strontium via ion exchange are, for example, strontium chloride (SrCl2), strontium nitrate (Sr(NO3)2), strontium acetate (Sr(CH3COO)2) and strontium acetylacetonate (Sr(acac)2).
[0088] Suitable yttrium salts for introducing yttrium via ion exchange are, for example, yttrium chloride (YCl), yttrium nitrate (Y(NO)), yttrium sulfate (Y(SO)), yttrium acetate (Y(CHCOO)), and yttrium acetylacetonate (Y(acac)).
[0089] Suitable titanium salts for introducing titanium via ion exchange are, for example, tetrabutyl orthotitanate (Ti(O(CH2)3(CH3))4) and ammonium hexafluorotitanate ((NH4)2TiF6).
[0090] Suitable zirconium salts for introducing zirconium via ion exchange are, for example, zirconium(II) chloride (ZrCl2), zirconium(III) chloride (ZrCl3), zirconium(IV) chloride (ZrCl4), zirconium(II) nitrate (Zr(NO3)2), zirconium(IV) nitrate (Zr(NO3)4), zirconium(IV) sulfate (Zr(SO4)2), and zirconyl chloride (ZrOCl2).
[0091] Suitable niobium salts for introducing niobium via ion exchange include, for example, niobium(IV) chloride (NBCl4), niobium(V) chloride (Nb2Cl 10 ), niobium oxalate (Nb(COO-COOH)5) and niobium(V) oxychloride (NbOCl3).
[0092] A suitable salt for introducing iron via ion exchange is Fe 2+ or Fe 3+The salt can be, for example, iron(III) chloride (FeCl3), iron(II) sulfate (FeSO4), iron(III) sulfate (Fe2(SO4)3, iron(III) nitrate (Fe(NO3)3), iron(II) acetate (Fe(CH3COO)2, iron(III) acetylacetonate (Fe(acac)3), and iron(II) fumarate (Fe(COO(CH)2(COO)2).
[0093] Suitable zinc salts for introducing zinc via ion exchange are, for example, zinc acetate (Zn(CHCOO)), zinc acetylacetonate (Zn(acac)), zinc chloride (ZnCl), zinc nitrate (Zn(NO) and zinc sulfate (ZnSO).
[0094] Suitable silver salts for introducing silver via ion exchange are, for example, silver nitrate (AgNO), silver acetate (Ag(CHCOO), silver acetylacetonate (Ag(acac)), silver oxide (AgO), and silver carbonate (AgCO).
[0095] Suitable lanthanum salts for introducing lanthanum via ion exchange are, for example, lanthanum carbonate (La2CO3)3), lanthanum chloride (LaCl3), lanthanum nitrate (La(NO3)3), lanthanum acetate (La(CH3COO)3), and lanthanum acetylacetonate (La(acac)3).
[0096] Suitable cerium salts for introducing cerium via ion exchange are, for example, cerium(III) chloride (CeCl3), cerium(III) sulfate (Ce2SO4)3), cerium(IV) sulfate (Ce(SO4)2), cerium(III) nitrate (Ce(NO3)3), cerium(III) acetate (Ce(CH3COO)3) and cerium(III) acetylacetonate (Ce(acac)3).
[0097] Suitable salts of praseodymium, neodymium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium are the chlorides, sulfates, nitrates, acetates and acetylacetonates of the trivalent cations Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu.
[0098] Suitable promethium salts for introducing promethium via ion exchange are, for example, promethium(III) chloride (PmCl3) and promethium(III) nitrate (Pm(NO3)3).
[0099] Suitable samarium salts for introducing samarium via ion exchange are, for example, samarium(III) chloride (SMCl3), samarium(III) acetate (Sm(CH3COO)3, samarium(III) carbonate (Sm2(CO3)3), samarium(III) nitrate (Sm(NO3)3), samarium(III) oxide (Sm2O3), samarium(III) sulfate (Sm2(SO4)3) and samarium(III) acetylacetonate (Sm(acac)3).
[0100] Suitable europium salts for introducing europium via ion exchange are, for example, europium(II) chloride (EuCl2), europium(III) chloride (EuCl3), europium(III) nitrate (Eu(NO3)3), europium(III) acetate (Eu(CH3COO)3) and europium(III) acetylacetonate (Eu(acac) 3 ).
[0101] The crystalline aluminosilicate small pore zeolite of the present invention is capable of removing NO from combustion exhaust gases. x In this process, also known as SCR (selective catalytic reduction), these zeolites can be used in processes to remove NO xThe use of the zeolite according to the invention as a catalytically active composition for converting NOx is therefore applicable to the exhaust purification systems of mobile and stationary combustion engines. Mobile combustion engines are, for example, gasoline and diesel engines as well as hydrogen internal combustion engines (H2ICE). The skilled person will understand that the combustion process usually takes place under oxidizing conditions and that any fuel can produce NO x and / or the combustion takes place in the presence of air, with the oxygen present in the air acting as an oxidant and at least a portion of the nitrogen present therein being converted to NO x We know that it can be oxidized to
[0102] The mobile combustion engine may be an engine for on-road and off-road applications, for example, gasoline and diesel engines, and also hydrogen internal combustion engines for passenger cars, agricultural machinery such as farm and forestry tractors and harvesters, construction wheel loaders, bulldozers, highway excavators, forklift trucks, road maintenance equipment, snowplows, ground support equipment at airports, aerial lifts and mobile cranes.
[0103] Stationary combustion engines are, for example, power plants, industrial heaters, cogeneration plants including wood-burning boilers, stationary diesel and gasoline engines, industrial and municipal waste incinerators, industrial drilling rigs, compressors, plants for the production of glass, steel and cement, plants for the production of nitrogen-containing fertilizers, plants for the production of nitric acid (e.g. plants applying the Ostwald process) and ammonia burners for fuelling the gas turbines for the production of nitric acid.
[0104] In a preferred embodiment, the crystalline aluminosilicate small pore zeolite according to the present invention is capable of converting NO from automobile combustion exhaust gases. x The exhaust gas may be used in a process for removing exhaust gases from a diesel or gasoline engine.
[0105] The object of the present invention is to provide an apparatus for treating exhaust gases from a combustion engine, comprising: x The problem is solved by a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NO x The SCR catalytically active composition for converting is a crystalline aluminosilicate zeolite according to the present invention.
[0106] In some embodiments of the SCR catalytically active composition according to the invention, the SCR catalytically active composition is present in the form of a coating on a support substrate, i.e., as a washcoat on the support substrate. The support substrate can be so-called honeycomb flow-through substrates and wall-flow filters, as well as corrugated substrates, wound or packed fiber filters, open-cell foams, and sintered metal filters. In a preferred embodiment, the support substrate is a honeycomb flow-through substrate or a honeycomb wall-flow filter.
[0107] The flow-through substrate and wall-flow filter may be made of inert materials such as silicon carbide, aluminum titanate, cordierite, metals or metal alloys. Such carrier substrates are well known to those skilled in the art and are available on the market. The corrugated substrate is made of ceramic E-glass fiber paper or metals or metal alloys. These are also well known to those skilled in the art and are available on the market.
[0108] When present in the form of a coating on a support substrate, the SCR catalytically active composition is typically present on or in the substrate in an amount of from about 10 to about 600 g / L, preferably from about 100 to about 300 g / L, calculated by weight of molecular sieve per volume of total catalyst article.
[0109] The SCR catalytically active composition can be coated on or to a substrate using known washcoating techniques. In this approach, the molecular sieve powder is suspended in a liquid medium along with a binder and a stabilizer. The washcoat can then be applied to the surface and walls of the substrate. The washcoat optionally also contains binders based on TiO2, SiO2, Al2O3, ZrO2, CeO2 and combinations thereof.
[0110] The washcoat may further optionally include additives. The additives may be present together with a binder as described above, or the washcoat may include only the binder or only the additives. Suitable additives include polysaccharides, polyvinyl alcohol, glycerol; polysaccharides having 2 or more carbon atoms in the chain, up to about 12 carbon atoms (C n ) wherein 2≦n≦12; a salt of a basic quaternary amine, wherein one or more of the quaternary amine groups are selected from the group consisting of n wherein 1≦n≦5, and the cation is equilibrated as a salt with one of the following anions, including but not limited to: hydroxide, fluoride, chloride, bromide, iodide, carbonate, sulfate, sulfite, oxalate, maleate, phosphate, aluminate, silicate, borate, or other suitable organic or inorganic counterion. salts of basic quaternary amines, which have been shown to be effective in treating cancer; inorganic bases selected from the list below, but not limited to: lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, and barium hydroxide; and simple salts of transition or rare earth elements, including, but not limited to, rare earth elements with atomic numbers 57 (La) to 71 (Lu) and, as mentioned above, nitrates, carbonates, sulfates, phosphates, borates, such as Sc, Y, Ti, Zr, and Hf.
[0111] In a preferred embodiment, the additive is a polysaccharide selected from the group consisting of galactomannan gum, xanthan gum, guar gum, curdlan, schizophyllan, scleroglucan, diutan gum, welan gum, starch, cellulose or alginates, or is derived from starch, cellulose (i.e. cellulosic) or alginates, and mixtures thereof. The cellulosic additive may be selected from the group consisting of carboxymethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, methylcellulose, methylhydroxyethylcellulose, methylhydroxypropylcellulose and ethylhydroxyethylcellulose.
[0112] More preferably, the additive is xanthan gum, guar gum or a mixture thereof. Even more preferably, the additive is xanthan gum.
[0113] When the first and / or second washcoat includes an additive, the additive is present in an amount of up to 20% by weight, preferably 3% to 15% by weight, more preferably 6% to 10% by weight, based on the total weight of the oxides, where "total weight of oxides" is the sum of the weights of the zeolite and the binder. It will be understood that when the washcoat does not include the binder, the "total weight of oxides" corresponds to the weight of the zeolite.
[0114] In other embodiments, the support substrates may be catalytically active in themselves and may further comprise a catalytically active composition, i.e. a crystalline aluminosilicate zeolite according to the invention. In addition to the catalytically active composition, these support substrates comprise a matrix component. In this context, all inert materials used in other processes for the production of catalytic substrates may be used as matrix components. These are, for example, silicates, oxides, nitrides or carbides, with magnesium aluminum silicate being particularly preferred.
[0115] In another embodiment of the SCR catalytically active composition according to the invention, the catalyst itself forms part of a support substrate, for example as part of a flow-through substrate or a wall-flow filter, such support substrate further comprising the matrix component described above.
[0116] The support substrates containing the SCR catalytically active composition according to the present invention may be used as is for exhaust gas purification. Alternatively, they may be coated with a catalytically active composition, for example, an SCR catalytically active composition. As long as these materials exhibit SCR catalytic activity, the SCR catalytically active compositions mentioned above are suitable materials.
[0117] In one embodiment, the catalytically active support material is produced by mixing 10% to 95% by weight of at least one inert matrix component with 5% to 90% by weight of the catalytically active composition, followed by extrusion of this mixture according to known procedures. As already mentioned above, in this embodiment, inert materials usually used for the production of catalytic substrates may be used as matrix components. Suitable inert matrix materials are, for example, silicates, oxides, nitrides and carbides, with magnesium aluminum silicate being particularly preferred. The catalytically active support material obtained by such a method is known as "extruded catalyzed substrate monolith". In the context of the present invention, an "extruded catalyzed substrate monolith" is an extruded monolith in which the catalytically active composition is a crystalline aluminosilicate zeolite with a maximum ring size of 8 tetrahedral atoms, the zeolite comprising copper, metal M1 and metal M2 as mentioned above.
[0118] The application of catalytically active components either onto an inert support substrate or onto a support substrate which is catalytically active alone, as well as the application of catalytically active coatings onto a support substrate, which support substrate comprises a catalyst according to the invention, can be carried out according to manufacturing processes well known to those skilled in the art, for example by the widely used dip-, pump- and suction-coating methods followed by a thermal after-treatment (calcination).
[0119] The skilled person knows that in the case of a wall-flow filter, the average pore size and the average particle size of the catalytically active component according to the invention may be adjusted to one another so that the coating thus obtained is located on the porous walls forming the channels of the wall-flow filter (on-wall coating). However, it is preferred that the average pore size and the average particle size are adjusted to one another so that the catalyst according to the invention is located within the porous walls forming the channels of the wall-flow filter. In this preferred embodiment, the inner surface of the pores is coated (in-wall coating). In this case, the average particle size of the catalyst according to the invention must be small enough to be able to penetrate into the pores of the wall-flow filter. A wall-flow filter coated with an SCR catalytically active composition is also known as "SDPF" (SCR on DPF, i.e. SCR catalytically active composition coated on diesel particulate filter) or "SCRF" (SCR on filter). The invention therefore encompasses a catalyzed substrate monolith, the monolith being a wall-flow filter and the SCR catalytic composition comprising a crystalline aluminosilicate zeolite according to the invention.
[0120] Further, the present invention encompasses an ammonia slip catalyst (ASC). It is well known to those skilled in the art that in exhaust gas purification systems, the ASC is preferably located downstream of the SCR since a discernible amount of NH3 exits the SCR based on dynamic operating conditions. Therefore, conversion of excess ammonia exiting the SCR is essential since ammonia is also an emission regulated gas. When ammonia is oxidized, NO is formed as the main product, which then reduces the NO2 emissions throughout the exhaust system. xThis contributes to a negative impact on the overall conversion of NO. Therefore, an ASC may be placed downstream of the SCR to mitigate further NO emissions. The ASC catalyst combines the basic NH3 oxidation function with the SCR function. Ammonia entering the ASC is partially oxidized to NO. As a result, the newly oxidized NO and NH3 in the ASC that have not yet been oxidized can react to N2 according to the normal SCR reaction scheme. In that way, the ASC can eliminate traces of ammonia by converting it to N2 in a parallel mechanism.
[0121] Those skilled in the art will understand that the SCR catalyst and the ASC catalyst may be present as two consecutive catalyst articles, or the SCR and ASC functional groups may be present on a single catalyst article. In the case of two consecutive catalyst articles, the upstream catalyst article is an SCR catalyst comprising a support substrate and a washcoat comprising an SCR catalytically active composition, and the downstream catalyst article is an ASC catalyst comprising a support substrate, a washcoat comprising an oxidation catalyst, and a washcoat comprising an SCR catalytically active composition. When the SCR catalyst and the ASC catalyst are present on one single substrate, a washcoat comprising the SCR catalytically active composition but not the oxidation catalyst is coated on the upstream zone of the support substrate, and the downstream zone of the support substrate comprises a lower layer having a washcoat comprising an oxidation catalyst and an upper layer having a washcoat comprising the SCR catalytically active composition. In all embodiments in which the SCR catalyst is combined with the downstream ASC catalyst, the SCR catalytically active composition of the SCR catalyst is preferably a crystalline aluminosilicate zeolite according to the present invention. The SCR catalytic active composition of the ASC can be selected from the crystalline aluminosilicate zeolite according to the present invention, the other zeolitic and non-zeolitic molecular sieves mentioned above, and mixed oxides containing vanadia and titania. When other zeolitic and non-zeolitic molecular sieves are used, they are preferably supported with at least one transition metal, preferably copper and / or iron. When a mixed oxide containing vanadia and titania is used, it may also optionally contain oxides of one or more elements selected from tungsten, silicon, aluminum, zirconium, molybdenum, niobium and antimony.
[0122] A platinum group metal may be used as an oxidation catalyst in the ASC and a zeolite may be used for the SCR function. The precious metal is a platinum group metal selected from ruthenium, rhodium, palladium, osmium, iridium, platinum and mixtures thereof. Preferably, the precious metal is selected from palladium, platinum, rhodium and mixtures thereof, more preferably, the precious metal is platinum. In a preferred embodiment, the platinum group metal is added to the washcoat slurry in the form of a precursor salt and applied to the support monolith. The platinum group metal is present in a concentration of 0.01 wt.% to 10 wt.%, preferably 0.05 wt.% to 5 wt.%, even more preferably 0.1 wt.% to 3 wt.%, calculated as the respective platinum group metal, based on the total weight of the washcoat support. In a preferred embodiment, the platinum group metal is platinum, which is present in a concentration of 0.1 wt.% to 1 wt.%, calculated as Pt, based on the total weight of the washcoat support.
[0123] In one embodiment, the ASC catalyst is a catalyzed substrate monolith, the monolith being a flow-through monolith coated with a bottom layer comprising an oxidation catalyst and a top layer comprising a crystalline aluminosilicate zeolite according to the present invention.
[0124] It is possible to use one or more of these SCR catalytically active compositions in all devices for the treatment of exhaust gases of combustion engines that contain a crystalline aluminosilicate zeolite according to the invention as an SCR catalytically active composition. If two or more SCR catalytically active compositions are present, they can be present in the form of two or more different layers, two or more different zones, as a mixture of two or more different SCR catalytically active compositions in one washcoat. Furthermore, the layers or zones may, independently of each other, comprise one single SCR catalytically active composition or a mixture of two or more SCR catalytically active compositions. Two or more crystalline aluminosilicate zeolites according to the invention are "different" if they differ in at least one parameter selected from framework type, SAR value, copper content, and / or metal M1 content and / or metal M2 content.
[0125] The present invention further provides an emissions treatment system for removing NOx emissions, and also optionally particulate matter, from an exhaust gas of an internal combustion engine, the system comprising, from upstream to downstream, in the following order: a) means for injecting ammonia or an ammonia precursor solution into the exhaust gas stream; b) NO in automobile combustion exhaust gas x A catalyzed substrate monolith comprising an SCR catalytically active composition for converting NO x and a catalyzed substrate monolith selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open cell foam, a sintered metal filter, and an extruded catalyzed substrate monolith.
[0126] It will be understood by those skilled in the art that if the substrate monolith is a flow-through monolith or a corrugated substrate, the corresponding catalyzed substrate monolith will only remove NOx emissions, however, if the substrate monolith is a wall-flow filter, the corresponding catalyzed substrate monolith will also remove particulate matter.
[0127] Those skilled in the art know that the SCR reaction requires the presence of ammonia as a reducing agent. Ammonia can be provided in a suitable form, for example in the form of liquid ammonia or in the form of an aqueous solution of an ammonia precursor, and can be added to the exhaust gas stream as required via a means for injecting ammonia or an ammonia precursor. Suitable ammonia precursors are, for example, urea, ammonium carbamate and ammonium formate. Alternatively, ammonia can be formed by catalytic reactions in the exhaust gas.
[0128] A widespread method is to deliver an aqueous urea solution and, if necessary, inject it into the catalyst of the present invention via an upstream injector and injection unit. Means for injecting ammonia, such as upstream injectors and injection units, are well known to those skilled in the art and can be used in the present invention without departing from the scope of the claims.
[0129] In addition, NO from the exhaust gas of the internal combustion engine x An exhaust treatment system for removing emissions, and optionally removing particulate matter, the system comprising: x The method includes the step of converting NO to SCR using a catalyzed substrate monolith comprising: x In the present invention, the SCR catalytically active composition for converting NO is a crystalline aluminosilicate zeolite according to the present invention. The system may further include additional catalytic articles, such as a diesel oxidation catalyst (DOC), an ammonia slip catalyst (ASC), a catalyzed or non-catalyzed particulate filter, a passive NO x Adsorbents (PNA) and / or Lean NO x It will be appreciated that the catalyzed particulate filter may include a diesel oxidation catalyst, thereby forming a "catalyzed diesel particulate filter (CDPF)" or may be coated with an SCR catalytically active composition, thereby forming an SDPF.
[0130] In one embodiment of the present invention, the emission treatment system including the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention is located in a proximal coupling position. The term "proximal coupling" refers to the location of the catalytic device in the exhaust gas treatment system of the engine that is less than one meter downstream of the exhaust gas manifold or turbocharger of the engine. In a preferred embodiment, the emission treatment system including the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention further comprises one or more particulate filters. In this embodiment, the "first" filter is the filter located most proximally to the engine. The "second" filter, if present, is located downstream of the first filter, immediately after the first filter or further downstream. In this embodiment, the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention is located in a proximal coupling position and is located upstream of the first filter.
[0131] As mentioned above, the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention can be a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam or a sintered metal filter. Preferably, the substrate monolith is a honeycomb flow-through substrate or a honeycomb wall-flow filter. When the catalyzed substrate monolith is a honeycomb wall-flow filter comprising the SCR catalytically active composition according to the present invention, it is referred to as an SDPF.
[0132] In yet another embodiment of the present invention, the emissions treatment system is located in an underfloor position. Underfloor catalyst members are also known in the prior art and are located downstream of any close-coupled and / or mid-coupled catalysts adjacent to the vehicle's muffler or under the vehicle's floor in combination with the vehicle's muffler. In this embodiment, a catalyzed substrate monolith comprising an SCR catalytically active composition according to the present invention is located downstream of the first filter. The substrate of the catalyzed substrate monolith comprising an SCR catalytically active composition according to the present invention is the same as described above for the close-coupled configuration.
[0133] In yet another embodiment of the invention, an emissions treatment system comprising a catalyzed substrate monolith comprising an SCR catalytically active composition according to the invention is located upstream of the first particulate filter but more than one meter downstream of the exhaust gas manifold or turbocharger of the engine. In this embodiment, the catalyzed substrate monolith comprising an SCR catalytically active composition according to the invention is preferably the first brick downstream of the exhaust gas manifold or turbocharger of the engine.
[0134] In yet another embodiment of the present invention, an emissions treatment system including a catalyzed substrate monolith comprising an SCR catalytically active composition according to the present invention is disposed downstream of a first particulate filter.
[0135] In those embodiments in which the catalyzed substrate monolith comprising the SCR catalytically active composition according to the present invention is located either upstream or downstream of the first particulate filter, the substrate monolith comprising the SCR catalytically active composition according to the present invention is the same as described above for the close-coupled and underfloor configurations.
[0136] The present invention further provides a method for removing NOx emissions, and also optionally particulate matter, from an exhaust gas of an internal combustion engine, the method comprising, from upstream to downstream, in the following order: a) injecting ammonia or an ammonia precursor solution into an exhaust gas stream; and b) introducing the exhaust gas from step a) into a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in vehicle combustion exhaust gas, the SCR catalytically active composition for converting NOx being a crystalline aluminosilicate zeolite according to the present invention, the substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.
[0137] As described above for the emissions treatment system, it will be understood by those skilled in the art that if the substrate monolith used in step b) of the above method is a flow-through monolith or a corrugated substrate, the corresponding catalyzed substrate monolith will only remove NOx emissions. However, if the substrate monolith used in step b) of the above method is a wall-flow filter, the corresponding catalyzed substrate monolith will also remove particulate matter. [Brief description of the drawings]
[0138] [Figure 1] The NOx conversion at 175° C. and N2O reduction at 400° C. are shown in percentage for CE1, CE4, Ex1, Ex3, and Ex5 after aging under NO only conditions. [Diagram 2] The NOx conversion rate at 175°C and the N2O reduction rate at 400°C are shown in percentage for CE1, Ex1, Ex3, and Ex5 aged at 175°C and 400°C under 25% NO2 conditions. [Diagram 3] The NOx conversion at 175°C and the N2O reduction at 400°C are shown in percentage for CE6, CE7, Ex5, Ex6, Ex12, Ex14 and Ex15 aged at 175°C and 400°C under 25% NO2 condition. [Figure 4] The NOx conversion at 175°C and the N2O reduction at 400°C are shown in percentage for CE8, CE9, CE10, Ex3, Ex4, Ex7, Ex8, Ex9, Ex10 and Ex16 aged at 175°C and 400°C under 25% NO2 condition.
[0139] Embodiment Comparative example 1 (CE1): CuCHA 11.5 g of copper(II) acetylacetonate (24.4 wt% Cu, ex Aldrich) was coarsely mixed with 96.5 g of CHA (SAR13.4) in a sealable plastic bottle of 250 mL capacity. Then, 10 g of Y-stabilized ZrO2 beads (5 mm diameter) were added. The bottle was sealed, fixed to a paint shaker (Olbrich Model RM500, 0.55 KW) and homogenized by shaking for 5 min. The bottle was then removed from the paint shaker and the mixture was passed through a coarse sieve to remove the beads. Finally, the mixed powder was transferred to a calcination vessel and heated in still air to 600 °C (ramp rate 5 °C / min) for 2 h.
[0140] The CHA thus obtained had a Cu:Al molar ratio of 0.21 and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0141] Comparative example 2 CE2(CE2):CuCHA 20.4 g of Cu(NO3)2·2.5H2O crystals were dissolved in 40 g of deionized water under stirring. The solution thus produced was added dropwise to 93.0 g of CHA (SAR 13.4) over a period of 15 min under constant stirring. The obtained powder was further dried in air at 80 °C for 4 h and then calcined in air at 600 °C for 2 h.
[0142] The CHA thus obtained had a Cu:Al molar ratio of 0.43 and a Cu content of 7.0 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0143] Comparative example 3 (CE3): CuCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 12.5 g of copper(II) acetylacetonate and 96.2 g of CHA (SAR 13.4).
[0144] The CHA thus obtained had a Cu:Al molar ratio of 0.23 and a Cu content of 3.8 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0145] Comparative example 4 (CE4): CuCaCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 11.3 g Ca(II) acetylacetonate hydrate, and 94.0 g CHA (SAR 13.4).
[0146] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Cu:Ca molar ratio of 1.0, a (Cu+Ca):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0147] Comparative example 5 (CE5): CuCaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 21.3 g Cu(NO3)2·2.5H2O, 3.1 g Ca(NO3)2·4H2O, and 95.7 g CHA (SAR 13.4).
[0148] The CHA thus obtained had a Cu:Al molar ratio of 0.43, a Ca:Cu molar ratio of 0.15, a (Cu+Ca):Al molar ratio of 0.49, and a Cu content of 7.0 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0149] Comparative example 6 (CE6): CuCaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 7.6 g Cu(NO3)2·2.5H2O, 4.2 g Ca(NO3)2·4H2O, and 96.5 g CHA (SAR 23.8).
[0150] The CHA thus obtained had a Cu:Al molar ratio of 0.25, a Ca:Al molar ratio of 0.14, and a Cu content of 2.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0151] Comparative Example 7 (CE7): CuCaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 7.6 g Cu(NO3)2·2.5H2O, 6.5 g Ca(NO3)2·4H2O, and 96.5 g CHA (SAR 17.5).
[0152] The CHA thus obtained had a Cu:Al molar ratio of 0.18, a Ca:Al molar ratio of 0.16, and a Cu content of 2.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0153] Comparative Example 8 (CE8): CuFeKCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 9.1 g Cu(NO3)2·2.5H2O, 2.6 g Fe(NO3)3·9H2O, 0.6 g KNO3, and 96.2 g CHA (SAR 13.4).
[0154] The CHA thus obtained had a Cu:Al molar ratio of 0.18, an Fe:Al molar ratio of 0.03, a (Cu+Fe):K molar ratio of 7, and a Cu content of 3.0 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0155] Comparative Example 9 (CE9): CuFeKCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·2.5H2O, 1.8 g Fe(NO3)3·9H2O, 0.7 g KNO3, and 95.8 g CHA (SAR 13.4).
[0156] The CHA thus obtained had a Cu:Al molar ratio of 0.21, an Fe:Al molar ratio of 0.02, a (Cu+Fe):K molar ratio of 7, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0157] Comparative example 10 (CE10): CuFeNaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 9.1 g Cu(NO3)2·2.5H2O, 2.6 g Fe(NO3)3·9H2O, 0.5 g NaNO3, and 95.8 g CHA (SAR 13.4).
[0158] The CHA thus obtained had a Cu:Al molar ratio of 0.18, an Fe:Al molar ratio of 0.03, a (Cu+Fe):Na molar ratio of 7, and a Cu content of 3.0 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0159] Example 1 (Ex1): CuCaBaCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 5.6 g Ca(II) acetylacetonate, 7.8 g Ba(II) acetylacetonate, and 93.6 g CHA (SAR 13.4).
[0160] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.50, a Ba:Cu molar ratio of 0.50, a (Cu+Ca+Ba):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0161] Example 2 (Ex2): CuCaBaCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 3.4 g Ca(II) acetylacetonate, 4.7 g Ba(II) acetylacetonate, and 93.7 g CHA (SAR 13.4).
[0162] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.30, a Ba:Cu molar ratio of 0.30, a (Cu+Ca+Ba):Al molar ratio of 0.34, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0163] Example 3 (Ex3): CuCaFeCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 5.6 g Ca(II) acetylacetonate, 7.8 g Fe(III) acetylacetonate, and 95.3 g CHA (SAR 13.4).
[0164] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.50, a Fe:Cu molar ratio of 0.50, a (Cu+Ca+Fe):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0165] Example 4 (Ex4): CuCaFeCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 3.4 g Ca(II) acetylacetonate, 4.6 g Fe(III) acetylacetonate, and 94.7 g CHA (SAR 13.4).
[0166] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.30, a Fe:Cu molar ratio of 0.30, a (Cu+Ca+Fe):Al molar ratio of 0.34, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0167] Example 5 (Ex5): CuCaSmCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 5.6 g Ca(II) acetylacetonate, 10.2 g Sm(III) acetylacetonate, and 94.8 g CHA (SAR 13.4).
[0168] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.50, a Sm:Cu molar ratio of 0.50, a (Cu+Ca+Sm):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0169] Example 6 (Ex6): CuCaSmCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 11.5 g copper(II) acetylacetonate, 3.4 g Ca(II) acetylacetonate, 6.1 g Sm(III) acetylacetonate, and 93.4 g CHA (SAR 13.4).
[0170] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.30, a Sm:Cu molar ratio of 0.30, a (Cu+Ca+Sm):Al molar ratio of 0.34, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0171] Example 7 (Ex7): CuCaFeCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 21.3 g Cu(NO3)2·2.5H2O, 5.2 g Ca(NO3)2·4H2O, 8.9 g Fe(NO3)3·9H2O, and 93.5 g CHA (SAR 13.4).
[0172] The CHA thus obtained had a Cu:Al molar ratio of 0.43, a Ca:Cu molar ratio of 0.25, a Fe:Cu molar ratio of 0.25, a (Cu+Ca+Fe):Al molar ratio of 0.65, and a Cu content of 7.0 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0173] Example 8 (Ex8): CuCaFeCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 21.3 g Cu(NO3)2·2.5H2O, 3.1 g Ca(NO3)2·4H2O, 5.3 g Fe(NO3)3·9H2O, and 94.7 g CHA (SAR 13.4).
[0174] The CHA thus obtained had a Cu:Al molar ratio of 0.43, a Ca:Cu molar ratio of 0.15, a Fe:Cu molar ratio of 0.15, a (Cu+Ca+Fe):Al molar ratio of 0.56, and a Cu content of 7.0 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0175] Example 9 (Ex9): CuCaFeCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 12.5 g copper(II) acetylacetonate, 6.1 g Ca(II) acetylacetonate, 8.4 g iron(III) acetylacetonate, and 91.0 g CHA (SAR 13.4).
[0176] The CHA thus obtained had a Cu:Al molar ratio of 0.23, a Ca:Cu molar ratio of 0.50, a Fe:Cu molar ratio of 0.50, a (Cu+Ca+Fe):Al molar ratio of 0.46, and a Cu content of 3.8 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0177] Example 10 (Ex10): CuCaFeCHA This material was prepared according to the method described in Comparative Example 1, except that the mixture contained 12.5 g copper(II) acetylacetonate, 8.6 g Ca(II) acetylacetonate, 5.1 g iron(III) acetylacetonate, and 93.2 g CHA (SAR 13.4).
[0178] The CHA thus obtained had a Cu:Al molar ratio of 0.23, a Ca:Cu molar ratio of 0.70, a Fe:Cu molar ratio of 0.30, a (Cu+Ca+Fe):Al molar ratio of 0.46, and a Cu content of 3.8 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0179] Example 11 (Ex11): CuSrCaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 5.2 g Ca(NO3)2·4H2O, 4.6 g Sr(NO3)2, and 93.0 g CHA (SAR 13.4).
[0180] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.5, a Sr:Cu molar ratio of 0.5, a (Cu+Ca+Sr):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0181] Example 12 (Ex12): CuCaCeCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 7.3 g Ca(NO3)2·4H2O, 5.7 g Ce(NO3)3·6H2O, and 92.5 g CHA (SAR 13.4).
[0182] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.7, a Ce:Cu molar ratio of 0.3, a (Cu+Ca+Ce):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0183] Example 13 (Ex13): CuCaZrCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 7.3 g Ca(NO3)2·4H2O, 3.3 g ZrO(NO3)2, and 92.5 g CHA (SAR 13.4).
[0184] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.7, a Zr:Cu molar ratio of 0.3, a (Cu+Zr+Ce):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0185] Example 14 (Ex14): CuCaYCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 7.3 g Ca(NO3)2·4H2O, 5.1 g Y(NO3)3·6H2O, and 92.5 g CHA (SAR 13.4).
[0186] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.7, a Y:Cu molar ratio of 0.3, a (Cu+Ca+Y):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0187] Example 15 (Ex15): CuCaLaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 7.3 g Ca(NO3)2·4H2O, 5.7 g La(NO3)3·6H2O, and 92.6 g CHA (SAR 13.4).
[0188] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Ca:Cu molar ratio of 0.7, a La:Cu molar ratio of 0.3, a (Cu+Ca+La):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0189] Example 16 (Ex16): CuMgFeCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 7.9 g Mg(NO3)2·6H2O, 5.3 g Fe(NO3)3·9H2O, and 92.5 g CHA (SAR 13.4).
[0190] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Mg:Cu molar ratio of 0.7, a Fe:Cu molar ratio of 0.3, a (Cu+Mg+Fe):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0191] Example 17 (Ex17): CuMgCaCHA This material was prepared according to the method described in Comparative Example 2, except that the mixture contained 10.6 g Cu(NO3)2·3H2O, 5.6 g Mg(NO3)2·6H2O, 5.2 g Ca(NO3)2·4H2O, and 94.3 g CHA (SAR 13.4).
[0192] The CHA thus obtained had a Cu:Al molar ratio of 0.21, a Mg:Cu molar ratio of 0.5, a Ca:Cu molar ratio of 0.5, a (Cu+Mg+Ca):Al molar ratio of 0.42, and a Cu content of 3.5 wt. %, calculated as CuO, based on the total weight of the zeolite.
[0193] Measurement of NOx conversion and N2O reduction The comparative examples and examples according to the invention listed above are xThe samples were tested for their reaction behavior in conversion and N2O reduction. The examples according to the invention were compared with zeolites containing only copper or only copper and calcium as metal M1, but no metal M2. These comparative tests show the low temperature performance and durability advantages of the invention for SCR applications. Measurements were performed using a conventional plug flow model. In these measurements, a gas stream simulating a lean combustion exhaust gas from an engine was passed over and through mesh particles of the test samples under various temperature conditions, and the effectiveness of the samples in reducing NOx was determined by an online FTIR (Fourier Transform Infrared) spectrometer. NO only and NO2 / NO x = 25%, two different test conditions were performed to simulate close-coupled and underfloor SCR catalyst locations, respectively.
[0194] Table 1 below details the complete experimental parameters used in generating the data contained herein.
[0195] [Table 1]
[0196] [Table 2]
[0197] The above data show that calcium alone acts as a good promoter for copper stabilization. However, the NO selectivity (percent) is still very high for zeolites promoted with copper and calcium only (CE1-CE7). By introducing a second element such as iron, cerium, zirconium, yttrium or lanthanum (Ex3, Ex12, Ex13, Ex14, Ex15), the NO selectivity (percent) can be significantly decreased. In addition, the NO selectivity (percent) at 175°C is significantly reduced. x An additional advantage in percent conversion was also observed.
[0198] FIG. 3 shows the NO2 concentration at 175°C for CE6, CE7, Ex5, Ex6, Ex12, Ex14, and Ex15 aged at 175°C and 400°C under 25% NO2 conditions. x The conversion and N2O reduction at 400°C are shown in percent, respectively. CE6 and CE7 are promoted with copper and calcium, but not with a third promoter metal. Ex5, Ex6, Ex12, Ex14 and Ex15 each further contain a third promoter metal that is a rare earth metal. These five examples according to the invention show significantly better NO2O reduction under both NO only and 25% NO2 conditions. x The results show lower conversion and lower N2O selectivity at 400° C. under NO only conditions. The N2O selectivity of Ex5 at 400° C. under 25% NO2 conditions is in the same range as that of CE6, while Ex6, Ex12, Ex14 and Ex15 show significantly lower N2O selectivity than both comparative examples.
[0199] FIG. 4 shows the NO2 concentration at 175°C for CE8, CE9, CE10, Ex3, Ex4, Ex7, Ex8, Ex9, Ex10 and Ex16 aged at 175°C and 400°C under 25% NO2 conditions. x The conversion and N2O reduction at 400°C are shown in percentages. CE8 and CE9 are promoted with copper, iron and potassium, and CE10 is promoted with copper, iron and sodium. In contrast, all examples according to the invention are promoted with copper, alkaline earth metal and iron, and differ only in their SAR values and / or the amounts of copper, iron and / or alkaline earth metal. The alkaline earth metal in Ex3, Ex4 and Ex7-Ex10 is calcium, and in Ex16 it is magnesium. All examples promoted with copper, iron and alkaline earth metal calcium show significantly better NOx conversion under both NO only and 25% NO2 conditions than the comparative examples in which the zeolite is promoted with copper, iron and alkali metal potassium or sodium. The N2O selectivity of Ex7 and Ex8 is comparable to that of CE8, CE9 and CE10 under both NO only and 25% NO2 conditions, but is significantly lower in the other examples according to the invention.
Claims
1. A crystalline aluminosilicate small pore zeolite having a maximum ring size of eight tetrahedral atoms, said zeolite comprising: copper, the Cu:Al atomic ratio being between 0.12 and 0.55, a metal M1, where M1 is calcium, magnesium or strontium and the M1:Cu atomic ratio is between 0.10 and 0.95, a metal M2 selected from magnesium, calcium, barium, strontium, yttrium, titanium, zirconium, niobium, iron, zinc, silver, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and mixtures thereof, with an M2:Cu atomic ratio between 0.05 and 0.80, wherein M1 and M2 are different from each other, the sum of the atomic ratio of copper, metal M1 and metal M2 to aluminum, (Cu+M1+M2):Al, is 0.20 to 0.80; The zeolite is a crystalline aluminosilicate small pore zeolite containing at least 2.5 wt. % copper, calculated as CuO, based on the total weight of the zeolite.
2. 2. The crystalline aluminosilicate small pore zeolite with a maximum ring size of 8 tetrahedral atoms according to claim 1, wherein the zeolite is selected from ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, BIK, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, ESV, ETL, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, THO, TSC, UEI, UFI, VNI, YUG, ZON, and mixtures and intergrowths thereof.
3. 2. A crystalline aluminosilicate small pore zeolite having a maximum ring size of eight tetrahedral atoms according to claim 1, wherein said zeolite is selected from AEI, CHA, AFX and LEV.
4. 2. The crystalline aluminosilicate small pore zeolite of claim 1, wherein the zeolite has a SAR value of 5-50.
5. 2. The crystalline aluminosilicate small pore zeolite of claim 1, wherein M1 is calcium or magnesium and M2 is selected from iron, cerium, zirconium, yttrium, samarium, strontium, lanthanum or barium.
6. A process for removing NOx from automobile combustion exhaust gas, comprising the crystalline aluminosilicate zeolite of any one of claims 1 to 5. x The process according to claim 1, wherein the active composition is used as an SCR catalyst for converting
7. A catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx for use in treating automobile combustion exhaust gases, wherein the SCR catalytically active composition for converting NOx is the crystalline aluminosilicate zeolite of claim 1.
8. 8. The catalyzed substrate monolith of claim 7, wherein the crystalline aluminosilicate zeolite is present in the form of a washcoat on a support substrate.
9. 9. The catalyzed substrate monolith of claim 8, wherein the support substrate is a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open cell foam, or a sintered metal filter.
10. 8. The catalyzed substrate monolith of claim 7, wherein the catalyzed substrate monolith is an extruded catalyzed substrate monolith.
11. 10. The catalyzed substrate monolith of claim 9, wherein the monolith is a flow-through monolith coated with an underlayer comprising an oxidation catalyst and an overlayer comprising the crystalline aluminosilicate zeolite of claim 1.
12. 1. An emissions treatment system for removing NOx emissions, and optionally also particulate matter, from an exhaust gas of an internal combustion engine, said system comprising, from upstream to downstream, in the following order: a) a means for injecting ammonia or an ammonia precursor solution into the exhaust gas stream; b) a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in automobile combustion exhaust gas, the SCR catalytically active composition for converting NOx being the crystalline aluminosilicate zeolite according to any one of claims 1 to 5, the substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open-cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.
13. The waste treatment system of claim 12 , wherein the waste treatment system is disposed in a proximal coupling position.
14. The emissions treatment system of claim 12 , wherein the emissions treatment system is located in an underfloor location.
15. 1. A method for removing NOx emissions, and optionally also particulate matter, from an exhaust gas of an internal combustion engine, said method comprising, from upstream to downstream, in the following order: a) injecting ammonia or an ammonia precursor solution into an exhaust gas stream; and b) introducing the exhaust gas from step a) into a catalyzed substrate monolith comprising an SCR catalytically active composition for converting NOx in automobile combustion exhaust gas, the SCR catalytically active composition for converting NOx being the crystalline aluminosilicate zeolite of any one of claims 1 to 5, the substrate monolith being selected from a honeycomb flow-through substrate, a honeycomb wall-flow filter, a corrugated substrate, a wound or packed fiber filter, an open cell foam, a sintered metal filter and an extruded catalyzed substrate monolith.
16. The internal combustion engine is a gasoline, diesel and hydrogen internal combustion engine (H 2 16. The method of claim 15, wherein the ICE is selected from the group consisting of: